Synergistic Effect of Proteinase Activity by Purification and Identification of Toxic Protease From Nemopilema nomurai - Yu, Chunlin; Li, Rongfeng; Yin, Xiujing; Yu, Huahua; Li, Pengcheng (Frontiers in Pharmacology, 2021)
Scyphozoan Nemopilema nomurai envenomation is an unresolved threat to human health in Asian waters. Nemopilema nomurai venom metalloproteinases (NnVMPs) play important toxicities in skin damage and inflammation, but there is still no purified protein for further studies. In this study, high proteinase activity fractions in tentacle autolysis were isolated by ammonium sulfate precipitation, DEAE Sepharose Fast Flow and Superdex 75 chromatography successively. Purification was guided by azocasein hydrolysis activity and SDS-PAGE. Final products were analyzed by LC-MS/MS. Four elution peaks purified by Superdex 75 chromatography had multiple protein bands but did not show proteinase activity. These fractions would recover proteinase activity by mixing again. Regulation mechanisms were speculated as binding metalloproteinase regulator or disaggregating metalloproteinase inhibitor by LC-MS/MS analysis. For the first time, a synergistic effect in Nemopilema nomurai proteinase activity was found in purification process.